Experimental investigations on solar chimney for optimal heat collection to be utilized in organic Rankine cycle. (15th September 2015) - Lee, Duen-Sheng; Hung, Tzu-Chen; Lin, Jaw-Ren; Zhao, Jun
Highlights: An innovative concept in integrating solar chimney with ORC is presented. The influences of several critical parameters on the solar chimney are discussed. Taguchi method reduced experimental simulations in finding optimal configuration. The temperature of the heat collected from solar chimney is successfully obtained. Abstract: The primary objective of this study was to propose an innovative approach for collecting the solar thermal energy from the concept of solar chimneys for electricity generation via organic Rankine cycles (ORCs). The influences of several critical parameters on the thermal performance and outlet temperature of solar chimneys were investigated. The parameters measured from the experiment were substantially reduced using Taguchi method. In addition, the optimal configurations of the solar chimney was identified, which are high-transmissivity glass, rectangular-tubes absorber plate, tilt angle of 45°, black polished surface, and airflow length of 4 m. The experimental results showed that the highest outlet temperature of air and heat collecting efficiency of solar chimneys were approximately 125 °C and 65%, respectively. In a feasibility analysis of ORC application, the system provides to the buildings with 12 kW h/day of electricity, and the area of the collector required was 41.0 m 2 . The experimental results indicated that the proposed method is feasible for solar chimney provide acceptable quality and quantity of heat for ORC.